Zig-Zag Midpoint Wag

Geometry Level 5

From vertex C C of a unit equilateral triangle A B C , ABC, we draw a line segment to the midpoint m 1 m_1 of the opposite side. From vertex m 1 m_1 of triangle B C m 1 , BCm_1, we similarly draw a line segment to the midpoint m 2 m_2 of the opposite side. Then we draw line segment m 2 m 3 m_2m_3 in triangle C m 1 m 2 , Cm_1m_2, and so on. We travel indefinitely in this manner, getting closer and closer to a destination point we call P . P.

If A P + B P + C P \overline{AP} + \overline{BP} + \overline{CP} can be expressed as a b ( e c + f d ) \dfrac{a}{b}\left(e\sqrt{c} + f\sqrt{d}\right) where a , b , c , d , e , f a,b,c,d,e,f are positive integers, gcd ( a , b ) = gcd ( e , f ) = 1 , \gcd(a,b) = \gcd(e,f) = 1, and c c and d d are distinct and square-free, input a + b + c + d + e + f a + b + c + d + e + f as your answer.


The answer is 19.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Mark Hennings
Jul 19, 2017

We have the recurrence relation m n = 1 2 ( m n 2 + m n 3 ) \mathbf{m}_n \; = \; \tfrac12(\mathbf{m}_{n-2} + \mathbf{m}_{n-3}) with the initial conditions m 0 = c \mathbf{m}_0 = \mathbf{c} , m 1 = 1 2 ( a + b ) \mathbf{m}_1 = \tfrac12(\mathbf{a} + \mathbf{b}) and m 2 = 1 2 ( b + c ) \mathbf{m}_2 = \tfrac12(\mathbf{b}+\mathbf{c}) , where a \mathbf{a} , b \mathbf{b} , c \mathbf{c} are the position vectors of A , B , C A,B,C respectively. This recurrence relation leads to the indicial equation 0 = 2 λ 3 λ 1 = ( λ 1 ) ( 2 λ 2 + 2 λ + 1 ) 0 \; = \; 2\lambda^3 - \lambda - 1 \; = \; (\lambda - 1)(2\lambda^2 + 2\lambda + 1) so the possible values of λ \lambda are 1 -1 , 1 2 ( 1 + i ) -\tfrac12(1+i) , 1 2 ( 1 i ) -\tfrac12(1-i) , and so m n = p + ( 1 2 ( 1 + i ) ) n q + ( 1 2 ( 1 i ) ) n r \mathbf{m}_n \; = \; \mathbf{p} + \big(-\tfrac12(1+i)\big)^n\mathbf{q} + \big(-\tfrac12(1-i)\big)^n\mathbf{r} for some vectors p \mathbf{p} , q \mathbf{q} , r \mathbf{r} . Of course, q \mathbf{q} and r \mathbf{r} will be complex conjugates, so that m n \mathbf{m}_n will turn out real.

Putting n = 0 , 1 , 2 n=0,1,2 gives us three equations for p \mathbf{p} , q \mathbf{q} , r \mathbf{r} . p + q + r = c p 1 2 ( 1 + i ) q 1 2 ( 1 i ) r = 1 2 ( a + b ) p + 1 2 i q 1 2 i r = 1 2 ( b + c ) \begin{aligned} \mathbf{p} + \mathbf{q} + \mathbf{r} & = \; \mathbf{c} \\ \mathbf{p} - \tfrac12(1+i)\mathbf{q} - \tfrac12(1-i)\mathbf{r} & = \; \tfrac12(\mathbf{a} + \mathbf{b}) \\ \mathbf{p} + \tfrac12i\mathbf{q} - \tfrac12i\mathbf{r} & = \; \tfrac12(\mathbf{b} + \mathbf{c}) \end{aligned} We only need to determine p = lim n m n \mathbf{p} \; = \; \lim_{n \to \infty} \mathbf{m}_n since that will be the position vector of the desired point P P . Elementary algebra gives us p = 1 5 a + 2 5 b + 2 5 c \mathbf{p} = \tfrac15\mathbf{a} + \tfrac25\mathbf{b} + \tfrac25\mathbf{c} .

Applying a coordinate system we have a = ( 1 2 1 2 3 ) , b = ( 0 0 ) , c = ( 1 0 ) \mathbf{a} \; = \; \binom{\tfrac12}{\tfrac12\sqrt{3}} \;, \; \mathbf{b} \; = \; \binom{0}{0} \;,\; \mathbf{c} \; = \; \binom{1}{0} and hence p = ( 1 2 1 10 3 ) \mathbf{p} \; = \; \binom{\tfrac12}{\tfrac{1}{10}\sqrt{3}} Thus A P = 1 2 3 1 10 3 = 2 5 3 AP = \tfrac12\sqrt{3} - \tfrac{1}{10}\sqrt{3} = \tfrac25\sqrt{3} , while B P = C P = 1 4 + 3 100 = 1 5 7 BP = CP = \sqrt{\tfrac14 + \tfrac{3}{100}} = \tfrac15\sqrt{7} , and hence A P + B P + C P = 2 5 ( 3 + 7 ) AP + BP + CP \; = \; \frac25(\sqrt{3} + \sqrt{7}) making the answer 2 + 5 + 1 + 3 + 1 + 7 = 19 2 + 5 + 1 + 3 + 1 + 7 = \boxed{19} .

Wow, I use barycenter to solve this, quite same.

Kelvin Hong - 3 years, 10 months ago

Log in to reply

Interesting! I used recurrence relation to solve this problem. I would like to see your solution. :)

Michael Huang - 3 years, 10 months ago

Log in to reply

Okay, I will post it later! Would you like to also post your solution?

Kelvin Hong - 3 years, 10 months ago

Since m 1 m_1 and m 2 m_2 are midpoints of A B \overline{AB} and B C \overline{BC} , m 1 m 2 \overline{m_1 m_2} is parallel to A C \overline{AC}

Similarly, m 2 m 3 \overline{m_2 m_3} is parallel to A B \overline{AB}

m 3 m 4 \overline{m_3 m_4} is parallel to B C \overline{BC}

m 5 m 6 \overline{m_5 m_6} or m 6 m 8 \overline{m_6 m_8} is parallel to A C \overline{AC}

m 6 m 7 \overline{m_6 m_7} is parallel to A B \overline{AB}

m 7 m 8 \overline{m_7 m_8} is parallel to B C \overline{BC}

So Δ m 6 m 7 m 8 \Delta m_6 m_7 m_8 is similar and has the same orientation as Δ A B C \Delta ABC

P P in Δ m 6 m 7 m 8 \Delta m_6 m_7 m_8 is still the same so m 6 P \overline{m_6 P} of Δ m 6 m 7 m 8 \Delta m_6 m_7 m_8 corresponds to A P \overline{AP} of Δ A B C \Delta ABC

Therefore, A A , m 6 m_6 , and P P must be on one line

Similarly, we can get B B , m 7 m_7 , and P P are collinear and C C , m 8 m_8 , and P P are collinear

Now using coordinates with A ( 1 2 , 3 2 ) A(\frac{1}{2},\frac{\sqrt{3}}{2}) , B ( 0 , 0 ) B(0,0) , and C ( 1 , 0 ) C(1,0) ,

We get m 6 ( 1 2 , 3 8 ) m_6(\frac{1}{2},\frac{\sqrt{3}}{8}) , m 7 ( 15 32 , 3 3 32 ) m_7(\frac{15}{32},\frac{3\sqrt{3}}{32}) , and m 8 ( 17 32 , 3 3 32 ) m_8(\frac{17}{32},\frac{3\sqrt{3}}{32})

Using these we can compute the lines

A m 6 \overleftrightarrow{A m_6} is x = 1 2 x=\frac{1}{2}

B m 7 \overleftrightarrow{B m_7} is y = 3 5 x y=\frac{\sqrt{3}}{5}x

and C m 8 \overleftrightarrow{C m_8} is y = 3 5 ( x 1 ) y=-\frac{\sqrt{3}}{5}(x-1)

They all intersect at P ( 1 2 , 3 10 ) P(\frac{1}{2},\frac{\sqrt{3}}{10})

So A P = 3 2 3 10 = 2 3 5 AP=\frac{\sqrt{3}}{2}-\frac{\sqrt{3}}{10}=\frac{2\sqrt{3}}{5}

And B P = C P = ( 1 2 ) 2 + ( 3 10 ) 2 = 7 25 = 7 5 BP=CP=\sqrt{(\frac{1}{2})^2+(\frac{\sqrt{3}}{10})^2}=\sqrt{\frac{7}{25}}=\frac{\sqrt{7}}{5} ( B P = C P BP=CP since P P is on the perpendicular bisector of B C BC which is x = 1 2 x=\frac{1}{2} )

Therefore, A P + B P + C P = 2 3 5 + 2 7 5 = 2 5 ( 3 + 7 ) AP+BP+CP=\frac{2\sqrt{3}}{5}+\frac{2\sqrt{7}}{5}=\frac{2}{5}(\sqrt{3}+\sqrt{7})

And a + b + c + d + e + f = 2 + 5 + 1 + 3 + 1 + 7 = 19 a+b+c+d+e+f=2+5+1+3+1+7=\boxed{19}

nice soln @Andres Rico M. III Gonzales

Romeo, Jr Madrona - 3 years, 10 months ago
Kelvin Hong
Jul 21, 2017

Relevant Wiki: Barycentric Coordinates

Using barycentric coordinates, found that

m 1 ( 0 , 0 , 1 ) m_1 (0,0,1) , m 2 ( 1 2 , 1 2 , 0 ) m_2 (\frac{1}{2},\frac{1}{2},0) , m 3 ( 0 , 1 2 , 1 2 ) m_3 (0,\frac{1}{2},\frac{1}{2}) .

So generalize to

m n = 1 2 ( m n 2 + m n 3 ) m_n=\frac{1}{2} (m_{n-2} + m_{n-3})

Using this, I want to do cancellation,

2 m 4 = m 2 + m 1 2m_4=m_2+m_1

2 m 5 = m 3 + m 2 2m_5=m_3+m_2

2 m 6 = m 4 + m 3 2m_6=m_4+m_3

2 m 7 = m 5 + m 4 2m_7=m_5+m_4

2 m 8 = m 6 + m 5 2m_8=m_6+m_5

. . . ...

2 m n 3 = m n 5 + m n 6 2m_{n-3}=m_{n-5}+m_{n-6}

2 m n 2 = m n 4 + m n 5 2m_{n-2}=m_{n-4}+m_{n-5}

2 m n 1 = m n 3 + m n 4 2m_{n-1}=m_{n-3}+m_{n-4}

2 m n = m n 2 + m n 3 2m_{n}=m_{n-2}+m_{n-3}

Summing all of this, and do some cancellation, we get

2 m n + 2 m n 1 + m n 2 = m 1 + 2 m 2 + 2 m 3 2m_n+2m_{n-1}+m_{n-2}=m_1+2m_2+2m_3

Here is the main point: When n approaches infinity, it includes m n = m n 1 = m n 2 m_n=m_{n-1}=m_{n-2}

So

5 m n = ( 1 5 , 2 5 , 2 5 ) 5m_n=(\frac{1}{5},\frac{2}{5},\frac{2}{5})

Return to normal xy-plane, let three verticle be ( 0 , 0 ) (0,0) , ( 1 , 0 ) (1,0) , ( 1 2 , 3 2 ) (\frac{1}{2},\frac{\sqrt{3}}{2})

According to the barycenter coordinate of point P, we know that P is below upper verticle 4 5 \frac{4}{5} of the height of triangle.

So the ordinary coordinate of P is ( 1 2 , 3 10 ) (\frac{1}{2},\frac{\sqrt{3}}{10}) .

Using simple formula we found that

A P + B P + C P = 2 5 ( 7 + 3 ) AP+BP+CP=\frac{2}{5} (\sqrt{7}+\sqrt{3})

So a + b + c + d + e + f = 19 a+b+c+d+e+f=\boxed{19} .

Interesting solution. :)

Michael Huang - 3 years, 10 months ago

Log in to reply

Thanks! :)

Kelvin Hong - 3 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...